Barriers to Health Care for Disabled People: A Review of the Literature from Low Income Countries - Chiluba, Brian Chanda (The Center for Disability Studies and Services Brawijaya University, 2019)
Over the years, they have been suggestions that people with disabilities face barriers when accessing health care services unlike their abled counter-parts. However, information regarding the nature of these barriers, especially for those in low income and middle income countries is not abundant and very sparse. signing of the United Nations Convention on the Rights of Persons with Disabilities on May 3, 2008 is one of the most important disability actions taken to date which marked national recognition of the rights for persons with disabilities, of which included access. The studies explored in this article review issues related to access to health care and those mostly used in areas within the Sub-Saharan as their sample site. The following document contains published studies that determine if disability limits access to health care and to attempt to identify what contextual factors (environmental and personal factors), interact with to limit this access. The findings were that people with disability who came from rural areas did find it harder to access healthcare than their urban counterparts. The major reason behind this is transportation from home to the health facility. A number of other reasons were also considered, such as no services were available.